Floating Drug Delivery Systems - JALEES AHMAD, FARHAN; DRABU, SUSHMA; DUREJA, HARISH; KHATRI, SMRITI (Asian Journal of Chemistry, 2010)
With the recent advances in the field of drug delivery, there had been increased interest in improving the efficacy of therapeutic agents through controlled oral drug delivery system, which are retained in the stomach for a prolonged and predictable period of time. Several approaches are currently used in the prolongation of gastroretentive drug delivery system (GRT). From the formulation and technical point of view, several approaches are currently utilized in the prolongation of the GRT, including floating drug delivery systems (FDDS), swelling and expanding systems, polymeric bioadhesive systems, modified-shape systems, high-density systems and other delayed gastric emptying devices. Floating drug delivery systems is considerably easy and logical approach for drugs which are poorly soluble at an alkaline pH, having narrow window of absorption, absorbed readily from gastrointestinal tract (GIT) and that are degrade in the colon. This review discusses the biological, pharmacokinetic and pharmacodynamic aspects of gastroretentive drug delivery system, various techniques, evaluation and in vitro-in vivo correlation of FDDS.